2002
DOI: 10.1590/s0101-81752002000600006
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and growth in adults of Macrobrachium acanthurus Wiegmann, (Decapoda, Palaemonidae) in a tropical coastal lagoon, Brazil

Abstract: ABSTRACT. MacrobrachiwlI acalllhurlls Wiegmann, 1836 is a Palaemonidae commonly found in Brazilian coastal environments. At Imboassica lagoon, located in the north of the State of Rio de Janeiro, it is found in two stages of its life cycle: as larvae and as reproductive adults. This work had as its goal the evaluation of adults distribution , estimating the weight/length relationship and the condition factor of these adults. After sampling in two regions of the lagoon, one interior and another closer to the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
3
11
0
3
Order By: Relevance
“…Previous studies have reported rapid growth rates in other species of Macrobrachium (Kanaujia et al 1997;Romero and Silva 2008;Alhassan and Armah 2011) (see review in Table 4 (1970) who reported an initial body size of 6.5 mm total body length (TL) and 27 mm TL for juveniles 40 days and two months after metamorphosis, respectively (data obtained from laboratoryreared specimens after larval development). Using previously published equations that relate CL to TL (CL ¼ 0.533 Â TL and CL ¼ 0.5043 Â TL in males and females, respectively: Albertoni et al 2002), our results fit well with those previously reported by Choudhury (1970) for males but not for females. An overestimation of the t 0 parameter, herein reported to be 0.77 in females versus 0.11 in males, might explain differences in initial body size between our study and that of Choudhury (1970).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have reported rapid growth rates in other species of Macrobrachium (Kanaujia et al 1997;Romero and Silva 2008;Alhassan and Armah 2011) (see review in Table 4 (1970) who reported an initial body size of 6.5 mm total body length (TL) and 27 mm TL for juveniles 40 days and two months after metamorphosis, respectively (data obtained from laboratoryreared specimens after larval development). Using previously published equations that relate CL to TL (CL ¼ 0.533 Â TL and CL ¼ 0.5043 Â TL in males and females, respectively: Albertoni et al 2002), our results fit well with those previously reported by Choudhury (1970) for males but not for females. An overestimation of the t 0 parameter, herein reported to be 0.77 in females versus 0.11 in males, might explain differences in initial body size between our study and that of Choudhury (1970).…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, the maximum body sizes herein reported for males and females are larger than those reported before for the same species. For instance, Valenti et al (1987) reported maximum body sizes of 138 mm TL (or 69.5 mm CL calculated using the equation that relates CL to TL: Albertoni et al 2002) and 108 mm TL (or 57.6 mm CL) in males and females, respectively. The reasons for dissimilarities between our results and those of Valenti et al (1987) remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of freshwater decapods in Brazil Atlantic coast has increased during the last decades, especially regarding their taxonomy, distribution (Bond-Buckup and Buckup, 1989;Magalhães, 2003;Magalhães et al, 2005;Mossolin and Mantelatto, 2008;Sampaio et al, 2009;Mossolin et al, 2016;Rocha and Bueno, 2011) and population structure (Ammar et al, 2001;Albertoni et al, 2002;Antunes and Oshiro, 2004;Mossolin and Bueno, 2002;Collins et al, 2006;Mattos and Oshiro, 2009). However, there is a lack of studies assessing effects of stream environmental variables on decapod communities in this area, which restricts our ability to conduct efforts for their conservation.…”
Section: Introductionmentioning
confidence: 99%
“…This species has the ability to adapt to different salinities from fresh to brackish waters, and needs marine conditions to complete its developmental cycle (Hughes & Richard, 1973;Dugger & Dobkin, 1975;Albertoni et al, 2002;Melo, 2003). It is omnivorous and feeds mainly during the night (Coelho, 1963;Carvalho, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Although the entire life cycle of this species is still under investigation, the knowledge of its biological aspects in Brazil is being accumulated over the recent years: population structure (Carvalho et al, 1979;Valenti, 1984;Müller et al, 1999), fecundity (Paiva & Costa, 1962;Valenti et al, 1989;Müller et al, 1992;Albertoni et al, 2002), geographical distribution (Coelho & Ramos-Porto, 1985), embryonic development (Müller et al, 2007) and molt cycles (Carvalho et al, 1979).…”
Section: Introductionmentioning
confidence: 99%